High Prevalence of Thoracic Aortic Dilatation in Men with Previous Inguinal Hernia Repair - Carlestål, Emelie; Thorell, Anders; Bergstrand, Lott; Wilamowski, Francis; Franco-Cereceda, Anders; Olsson, Christian (AORTA, 2022)
Background Identifying a useful marker for thoracic aortic dilatation (TAD) could help improve informed clinical decisions, enhance diagnosis, and develop TAD screening programs. Inguinal hernia could be such a marker. This study tested the hypothesis that the thoracic aorta is larger and more often dilated in men with previous inguinal hernia repair versus nonhernia controls.Methods Four hundred men each with either previous inguinal hernia repair or cholecystectomy (controls) were identified to undergo chest computed tomography to measure the diameter of the thoracic aorta in the aortic root, ascending, isthmic, and descending aorta and to provide self-reported health data. Presence of TAD (root or ascending diameter > 45 mm; isthmic or descending diameter > 35 mm) and thoracic aortic diameters were compared between groups and associations explored using uni- and multivariable statistical methods.Results Complete data were obtained from 470/718 (65%) eligible participants. TAD prevalence was significantly higher in the inguinal hernia group: 21 (10%) versus 6 (2.4%), p = 0.001 for proximal TAD, 29 (13%) versus 21 (8.3%), p = 0.049 for distal TAD, and 50 (23%) versus 27 (11%), p < 0.001 for all aortic segments combined. In multivariable analysis, previous inguinal hernia repair was independently associated with dilatation of the proximal aorta (odds ratio 5.3, 95% confidence interval 1.8–15, p = 0.003). Contrarily, mean thoracic aortic diameters were similar (root and ascending aorta) or showed clinically irrelevant differences (isthmus and descending aorta).Conclusion TAD, but not increased aortic diameters on average, was common and significantly more prevalent in men with previous inguinal hernia repair. Hernia could be a marker condition associated with increased prevalence of TAD. Ultimately, TAD screening could consider hernia as a possible selection criterion.
Keywords: thoracic aortic aneurysm; inguinal hernia; risk factors; screening